A new genus of hawker dragonfly (Odonata: Anisoptera: Aeshnidae) from the Early Eocene Fur Formation of Denmark - Bechly, Günter; Rasmussen, Jan Audun (Zootaxa, 2019)
A new genus and species of fossil hawker dragonfly, Parabaissaeshna ejerslevense gen. et sp. nov. (Aeshninae: Allopetaliini), is described from the Early Eocene Fur Formation (Mo-clay) of the island of Mors, northern Denmark. Its position among traditional “gomphaeschnine” dragonflies is discussed, and it is attributed to the tribe Allopetaliini as close relative to the Cretaceous genus Baissaeshna, documenting the survival of this lineage through the K-Pg mass extinction. The Recent genus Boyeria and the Eocene genus Anglogomphaeschna are also transferred to Allopetaliini.